Functional and characterisation of multi-strain probiotics in encapsulated and non-encapsulated forms of water kefir - Lew, Yong Yi (2025)
Probiotics are living microorganisms known for their health benefits in maintaining gut health. It is empirically proven with better efficacy in multi-strain formulation than single-strain formulation. In this study, we aimed to evaluate antimicrobial, hydrophobicity, auto-aggregation, co-aggregation, acid and bile tolerance, cold tolerance, and ultrasound cavitation tolerance of a novel multi-strain formulation. Based on the result, the multi-strain formulation showed a superior antimicrobial effect on Escherichia coli (80% inhibitory effect) and the least effect on Bacillus subtilis (43.33%). On the other hand, yeast strain exhibited the highest acid tolerance, achieving a 42.52% survival rate, while lactic acid bacteria (LAB) had the lowest (32.02%). Similarly, bile tolerance tests indicated the highest survival in yeast (115.38%) and the lowest in LAB (31.42%) at 2% (w/v). Moreover, ultrasound treatment revealed an increasing growth trend under wattages, with LAB achieving its peak at 64W for 6 min (2.91±0.04). At 4℃ storage conditions, the encapsulated LAB showed the highest viable rate (64.96%), while yeast had only 21.65%. Additionally, encapsulation significantly enhanced hydrophobicity, with encapsulated probiotics showing 43.03% compared to non-encapsulated forms (24.20%). However, non-encapsulated probiotics auto-aggregation rates were higher (82.95% at 24 hours) than encapsulated forms (46.89%). Co-aggregation assays revealed pathogen-binding capacities for Serratia marcescens (40.74%) and Escherichia coli (15.28%). Overall, our study demonstrated that encapsulated multi-strain formulation has fulfilled the overall requirements for probiotic product standards. This first study that evaluates the multi-strain formulation can serve as future research groundwork.